Long-term safety assessment of niraparib in patients with recurrent ovarian cancer: results from the ENGOT-OV16/NOVA trial. (1st November 2019) - Mirza, MR; Dørum, A; Benigno, B; Mahner, S; Bessette, P; Bover Barcelo, IM; Berton, D; Ledermann, J; Rimel, BJ; Herrstedt, J; Lau, S; Canzler, U; et al.
Abstract : Introduction/Background: Niraparib is a poly(ADP-ribose) polymerase inhibitor (PARPi) approved in the United States and Europe for maintenance treatment of patients with recurrent ovarian, fallopian tube, or primary peritoneal cancer (ROC) following complete or partial response to platinum-based chemotherapy. Here, we present long-term safety data of niraparib, reporting the incidence of treatment-emergent adverse events (TEAEs) among patients in the ENGOT-OV16/NOVA trial. Methodology: ENGOT-OV16/NOVA enrolled 553 patients with ROC who received 2–3 prior lines of platinum-based chemotherapy. Patients were randomised 2:1 to receive niraparib (300 mg once daily) or placebo in independent germline BRCA -mutated (g BRCA mut) or non-g BRCA mut cohorts. We report TEAE incidence monthly for the first 6 months and for months 7–12 combined. After month 12, we report TEAEs to the safety data cutoff of September 2017. Results: Overall, 367 patients received niraparib 300 mg once daily. Dose reductions due to TEAEs were highest in month 1 (34%). In month 5, only 7% of patients required dose reductions. The incidence of any-grade and grade ≥3 haematologic and symptomatic TEAEs decreased each month in the first 6 months and remained low thereafter. Incidence of grade ≥3 thrombocytopenia was highest in month 1 (28%) and decreased to 10% and 5% at months 2 and 3, respectively. Treatment discontinuations due to TEAEs were <5% in each month and time interval measured. Conclusion: The incidence of haematologic and symptomatic TEAEs decreased quickly over the first 3 months and continued to decrease over the duration of the trial. Dose reductions and grade ≥3 thrombocytopenia events were highest in month 1 and decreased rapidly thereafter. Treatment discontinuations due to TEAEs were <5% for all months and time intervals measured. These data demonstrate the importance of appropriate dose selection and support the safe, long-term use of niraparib for maintenance treatment in patients with ROC. Disclosure: AD, IMBB, DB-R, JH, EK, JB, PD, IB, SL: Nothing to disclose WG, SH, FdJ: Employee of Tesaro MRM: Consulting for Clovis, AstraZeneca, Tesaro BB: Honoraria from AstraZeneca, Insys, Funding from Tesaro SM: Grant and Personal Fees from Tesaro, AstraZeneca, Medac, MSD, PharmaMar, Roche, Teva. Personal Fees from Clovis, Sensor Kinesis PB: Site payment for clinical trial conduct from Tesaro JL: Ad Boards and PI for trials with AstraZeneca, Clovis, Pfizer. Ad Boards for Roche. Clinical Trials with MSD/Merck. BJR: Consulting with AstraZeneca, Tesaro, Genentech/Roche. Honoraria from Genentech UC: Honoraria and fees for consulting and Ad boards from Roche, AstraZeneca IPV: Travel and Accomodations from PharmaMar, Roche. Expert Testimony for AstraZeneca. Research Funding from Novartis, Tesaro DL: Ad Board for Tesaro, Clovis, AstraZeneca. Research Support from Clovis. Study Conduction support from Tesaro and PharmaMar UAM: Consulting for Merck KGaA, Clovis, Geneos, Eli Lilly, 2x Oncology